A Study of Perceptual Skills in Arabic-speaking School-aged Children - Almoussabi, Eman Haidar; Priyadarshi, Brajesh (JOURNAL OF INDIAN EDUCATION, 2022)
The auditory and visual perceptual skills (AVPS) are looked at as essential components in the progression of early reading skills (ERS) that form the basis for later academic success. The current study aimed at examining the sequential acquisition of the continuum of perceptual skills in Arabic-speaking school-aged children ranging from grade I to grade VIII. An overall number of 480 typically developing children were equally selected from the government and private schools. The descriptive analysis revealed that both male and female participants of the two schools showed same performance across all the sections. Results revealed that statistically significant differences existed in the performance of children of government school (lower socioe-conomic status— LSES) compared to children of private school (higher socioe-conomic status— HSES). Results also revealed a significant difference in the performance of students of different grades. The performance of children improved from the lower grades to the higher grades across all the sections.